Analysis of the Natural Aging of Silver Fir (Abies alba Mill.) Structural Timber Using Dendrochronological, Colorimetric, Microscopic and FTIR Techniques - Dremelj, Matjaž; Novak, Klemen; Merela, Maks; Straže, Aleš (Forests, 2023)
Timber, as a building material, is subject to structural changes in the used interior, which result from the influence of various local environmental conditions and their changes during the service life. Samples of naturally aged historic silver fir (Abies alba Mill.) wood were taken from the roof of St. Barbara Church (Ravnik above Hotedršica, Slovenia). The slices of historic wood were dendrochronologically dated and analyzed by CIELab color determination, light microscopic analysis and IR spectroscopy. Our results showed that the interior of the 18th-century fir structural timber had lower color lightness (L*) and intensity (b*), particularly in the latewood. The partial increase in lignin and decrease in hemicelluloses relative to cellulose content, associated with an increased degree of crystallinity of cellulose, was confirmed by epifluorescence and polarized light microscopy combined with FTIR spectroscopy.